The contribution of psychological factors on Jakarta’s communities disaster preparedness in facing the drowning threats - Shofia, Leila Alya; Avrilla, Nesha Sawwa; Nurunnada, Dzakia Rahmah; Saputri, Lola Eka; Gazadinda, Rahmadianty (MEDIA ILMU KESEHATAN, 2024)
Background: The risk of flooding in Jakarta is continuously increased and predicted to be drowned in 2050. Unfortunately, citizens seem to have no feeling of uneasiness although their place is haunted by the drowning threats. Objective: This study aims to investigate the impact of risk perception, self-efficacy, trust in government, and place attachment to disaster preparedness facing the threat of drowning.Methods: A cross sectional study with quantitative and non-experimental design was applied. 486 Jakarta’s citizens as the sample of the study by using quota sampling. Moderated Regression Analysis (MRA) was executed to test the hypothesis.Results: Risk perception, self-efficacy, and trust in government were found significantly affected disaster preparedness with a total contribution of 24% (F=10.81, sig < 0.000) after being moderated by place attachment.Conclusion: This study demonstrated that place attachment was capable of modifying the role of risk perception, self-efficacy, and trust in government in predicting disaster preparedness. This finding implies the necessity of considering an individual's attachments toward their living place while intervening the disaster preparedness.